FACTORS OF HEALTH BEHAVIOUR OF ADOLESCENTS IN THE INNER CITY OF UYO, AKWA IBOM STATE - Okediji, A. Enwongo; Imbur, Moses T; Jonah , U. Miracle; Ikoroha , S. Innocent (Global Journal of Medical and Health Science, 2024)
This study investigated the impact of school type, internet use, and sexual initiation on the health behaviors of adolescents in an inner city setting. Data were collected from two secondary schools (Nuco Secondary School off Ikpa road and Four towns Secondary School off Abak road). One hundred and ninety-two (192) participants consisting of 86 (44.8%) males and 106(55.2%) females aged 14 to 21 years with a mean age of 16.70 years were selected using the convenience sampling technique. Two instruments were adopted in this study; the Internet Usage Scale (IUS) and Health Behavior Checklist scale (HBCS), and were used to collect data in the study. This study used a correlation design. Pearson Product Moment Correlation Coefficient (Pearson r) and independent t-test statistics were used to analyze the data collected. Result revealed that Gender was significantly associated with the health behaviors of adolescents (r (192) = 0.24, p< 0.01). Result also revealed that school type was significantly associated with the health behavior of adolescents (r (192) =.36, p<0.01). Result also revealed that Internet usage was significantly associated with the health behaviors of adolescents (r (192) =0.55, p< 0.01). Additionally, the result revealed that there was a significant difference between the health behaviors of female adolescents who initiated sex earlier than their male counterparts (t (19) =2.01, p< 0.05). Implications and recommendations for further studies are presented